2015
DOI: 10.1016/j.agee.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation, fiber separation, decomposition, and nutrient release of secondary-forest biomass, mechanically chopped-and-mulched, and cassava production in the Amazon

Abstract: No-tillage planting in mechanically-chopped secondary-forest seeks to replace slash-and-burning agriculture. We evaluated the effect of horizontal (HC) and vertical (VC) chopping-and-mulching mechanisms on vegetation fragmentation and decomposition rate and nutrient release from chopped residue, and on cassava production in eastern Amazon. Chopped-and-mulched residue was classified into four residue-size (Fs 1 = 1-7, Fs 2 = 7-25, Fs 3 = 25-35, and Fs 4 = >35 mm) and six residue-type (with husk/ bark -WB, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
2
13
0
2
Order By: Relevance
“…Nesse caso, os autores também associaram a redução do N à absorção desse elemento e imobilização na biomassa acima do solo, já que o N é um dos macronutrientes que concentram maiores teores nas acículas em distintos estádios fenológicos (VIERA; SCHUMACHER, 2009). Logo, a manutenção de resíduos vegetais tem uma contribuição fundamental para a ciclagem de nutrientes e manutenção da fertilidade do solo em sistemas florestais ou agroflorestais (REICHERT et al, 2015). 462 FLORESTA,Curitiba,PR,v.…”
Section: Nitrogênio Total E Carbono Orgânico Totalunclassified
“…Nesse caso, os autores também associaram a redução do N à absorção desse elemento e imobilização na biomassa acima do solo, já que o N é um dos macronutrientes que concentram maiores teores nas acículas em distintos estádios fenológicos (VIERA; SCHUMACHER, 2009). Logo, a manutenção de resíduos vegetais tem uma contribuição fundamental para a ciclagem de nutrientes e manutenção da fertilidade do solo em sistemas florestais ou agroflorestais (REICHERT et al, 2015). 462 FLORESTA,Curitiba,PR,v.…”
Section: Nitrogênio Total E Carbono Orgânico Totalunclassified
“…Chop-and-mulch, a fire-free technique for land preparation (Denich et al, 2004), conserves nutrients, improves soil quality, and reduces carbon dioxide-equivalent emissions from the soil to the atmosphere in comparison to slash-and-burn, as shown by studies conducted in eastern Amazonia (Sommer et al, 2004;Davidson et al, 2008;Comte et al, 2012;Reichert et al, 2015Reichert et al, , 2016). However, chop-and-mulch has not always increased soil carbon stocks (Perrin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental design was completely randomized, with three treatments and five replications, with the following management systems: traditional area of management "slash-and-burn" (SB); alternative management "slash-and-mulch" (SM); and adjacent secondary vegetation as a reference area (SV (Reichert et al, 2015b).…”
Section: Methodsmentioning
confidence: 99%
“…In tropical conditions, Po is of great importance to P conservation in soils (Cunha et al, 2007). In a study that assessed the fragmentation, decomposition and nutrient release of biomass from shredded secondary forest in the Amazon, Reichert et al (2015b) observed a reduction in residual P in the crushed plant material and their release in soil solution, probably because the P concentration in plant tissue primarily occurred in cell vacuoles as inorganic P and monoesters (Giacomini et al, 2003), which are highly soluble forms. (Bowman and Cole, 1978a;Bowman, 1989).…”
Section: Available Phosphorus (P-mehlich)mentioning
confidence: 99%